Changes in journalism versus changes in journalism education - Brikše, Inta (Žurnalistikos tyrimai, 2009)
This paper is focused on journalism education in the context of changes in journalism, the professionalization of journalism, and the study programmes that are offered by universities. The author has relied on self-evaluation reports from three study programmes in Latvia, the Evaluation commission final reports, and the things which students themselves have had to say about theirknowledge and skills in comparison to what is needed to work as a journalist.Keywords: journalism, education, professional standards.